(untitled) (SUSTAINCOM Journal of Sustainable International Community Service Frequency, 2026)
igital marketing socialization for leather puppet handicraft micro, small and medium Enterprises (MSME) in Wukirsari Village, Bantul, Yogyakarta is important. Despite its high cultural value, the marketingof shadow puppet product its still limited to tradional methods,making it difficult to reach a wider market, especially the younger generation and the global market. This study used a qualitative approach with a case study method, through interview, observation, and documentation of local MSME players. The result showed that limited understanding of technology, lack of training, and internet access constraints are the main challenges in the adoption of digital marketing. The socialization of digital marketing has proven to have a positive impact in increasing knowledge, skills, and the spirit of adaptation to technological developments. Through the utilization of social media, marketplace, and websites, MSME players can expand their market while preserving local culture in a more modern and relevant fprm. Thus, the socialization of sustainable digital marketing is an important strategy to improve the competitiveness of leather puppet MSME in the digital era.